2018
DOI: 10.1136/bcr-2017-224133
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of fulminant neonatal enteroviral myocarditis in monochorionic diamniotic twins with cardiopulmonary support, intravenous immunoglobulin and pocapavir

Abstract: Neonatal cardiogenic shock most commonly occurs due to critical congenital heart disease, sepsis, metabolic disorder or arrhythmias. In particular, enterovirus infections are common in the neonatal period, and patients can present with fulminant myocarditis. Early recognition is imperative due to its high morbidity and mortality without prompt and aggressive treatment. We present the successful treatment of fulminant neonatal enteroviral myocarditis in a pair of monochorionic diamniotic twins with cardiopulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In the past two decades, B19V and HHV6 have been more frequently detected in EMB samples from patients with myocarditis than enteroviruses or adenoviruses, and approximately 30% of patients have multiple viral infections 10 , 14 . In infants, a high number of cases of acute enterovirus myocarditis has been observed in the past 5 years 15 17 . In general, the detection frequency of the viruses associated with inflammatory cardiomyopathy has changed over time, partly influenced by the evaluation of a broader repertoire of viruses (Fig.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the past two decades, B19V and HHV6 have been more frequently detected in EMB samples from patients with myocarditis than enteroviruses or adenoviruses, and approximately 30% of patients have multiple viral infections 10 , 14 . In infants, a high number of cases of acute enterovirus myocarditis has been observed in the past 5 years 15 17 . In general, the detection frequency of the viruses associated with inflammatory cardiomyopathy has changed over time, partly influenced by the evaluation of a broader repertoire of viruses (Fig.…”
Section: Pathogenesismentioning
confidence: 99%
“…Trial participants with enterovirus-positive myocarditis or adenovirus-positive myocarditis (as assessed with EMB) showed viral clearance after treatment with IFNβ 26 , 260 , but IFNβ therapy was not associated with viral DNA clearance in patients with B19V-positive myocarditis 146 , 260 . The antiviral drugs pocapavir and pleconaril as well as IVIG therapy are effective in neonates with enteroviral myocarditis 15 17 . In patients with latent infection with Epstein–Barr virus, cytomegalovirus or HHV6, the use of anti-herpesvirus drugs is an option to reduce viral copy numbers 261 .…”
Section: Therapymentioning
confidence: 99%
“…Members of a class of antienteroviral compounds known as capsid inhibitors exert their antiviral effect by inserting into the hydrophobic pocket in the virus canyon and replacing a lipid pocket factor, thereby preventing virus uncoating (29)(30)(31). Recently completed clinical trials of capsid inhibitors pleconaril and pocapavir have demonstrated safety and efficacy (32,33), and studies using pocapavir as a treatment for enterovirus infection in neonates have shown some success (34)(35)(36). Recently, a novel early-stage capsid inhibitor, 4-dimethylaminobenzoic acid (4EDMAB), was shown to inhibit replication of coxsackievirus B3 (CVB3) with a mechanism targeting the capsid outside the typical binding pocket (37).…”
Section: Figmentioning
confidence: 99%
“…Reasons to suspect a genetic susceptibility in infectious myocarditis may derive from twin studies (usually newborn or children) [16][17][18], familial clustering suggesting genetic determinants or predisposing genetic factors [19][20][21], and rare Mendelian diseases [22,23] as well as endemic infections linked to both pathogen and population genetic make-up [24]. The topic must be discussed with caution so as not to transform infectious diseases into genetic ones, especially as the distinction between genetic susceptibility from exclusive environmental factors that might aggregate within families can be difficult.…”
Section: Infectious Myocarditis and Geneticsmentioning
confidence: 99%